PENGARUH DEDIKASI DAN JAMINAN KESEJAHTERAAN TERHADAP KINERJA GURU MADRASAH TSANAWIYAH PEKANBARU - Mirawati Mirawati; Wiwik Mariana (POTENSIA: Jurnal Kependidikan Islam, 2021)
The low performance of teachers in learning at Madrasah Tsanawiyah Pekanbaru is a problem in this study. This can be seen from the results of the National Examination that Madrasah is lower than SMP which can be seen from the average score of graduates. MTs UN results 65.5 and SMP results 81.35. Factors that affect teacher performance are teacher dedication and welfare guarantees. The purpose of this study was to examine the effect of dedication and welfare insurance on the performance of Madrasah Tsanawiyah Pekanbaru teachers. This research is a correlation study with three variables, two independent variables, namely teacher dedication and welfare and one guarantee variable, namely teacher performance. Respondents in this study were teachers of Madrasah Tsanawiyah Pekanbaru with a total sample of 123 people. The instruments used in this study were observation, questionnaires and documentation. To analyze the data, simple and multiple linear regression were used. After processing the data using SPSS version 23 with simple and multiple linear regression tests, it was found that there was a significant influence between teacher dedication on teacher performance with an effect of 51.2%, the effect of welfare insurance on teacher performance by 31%, the effect of dedication and welfare guarantees on teacher performance by 51.3%. Based on the partial analysis, it is also proven that there is a correlation between all the independent variables purely on the dependent variable. In other words, dedication and welfare insurance are interrelated without being influenced by other variables. it means that dedication has a relationship with teacher performance without being influenced by welfare insurance (correlation coefficient 0.698, partial correlation coefficient 0.361). Likewise, welfare guarantees on performance have a relationship without being influenced by dedication (correlation coefficient 0.557, correlation coefficient 0.310). So that there is no change to the predetermined hypothesis